Profil Kondisi Fisik Atlet Bola Voli STKIP PGRI Pacitan - Probo Ismoko, Anung; Putro, Danang Endarto (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The aim of the study was to determine the physical condition profile of STKIP PGRI Pacitan Bola voli athletes who competed in the East Java POMPROV championship in 2023. The athlete's physical condition used as a benchmark to determine whether the athlete was ready before competing. Materials and methods. The study used a survey description method with test and measurement techniques. The research population used was all STKIP PGRI Pacitan indoor volleyball athletes who competed in the East Java POMPROV Championship in 2023. The measuring instruments: sit-up test, sit and reach test, vertical jump test, 20 m run test, and multi-stage fitness test. The data analysis technique used a Likert scale. Result. The results of data analysis in this study as a whole show that 0% of athletes had a physical profile in the very good category, 85.72% (12 athletes) had a physical profile in the good category, 7.14% (1 athlete) had a physical profile in the moderate category, 7.14% (1 athlete) had a physical profile in the less category, and 0% had a physical profile in the very poor category. Conclusions. The conclusion of the study is that the physical condition of STKIP PGRI Pacitan volleyball athletes who would take part in the POMPROV Championship in 2023 East Java as a whole was in a good category so that athletes were declared physically ready to take part in the championship.